Desensitization, Trafficking, and Resensitization of the Pituitary Thyrotropin-Releasing Hormone Receptor - Hinkle, Patricia M.; Gehret, Austin U.; Jones, Brian W. (Frontiers in Neuroscience, 2012)
The pituitary receptor for thyrotropin-releasing hormone (TRH) is a calcium-mobilizing G protein-coupled receptor (GPCR) that signals through Gq/11, elevating calcium and activating protein kinase C. TRH receptor signaling is quickly desensitized as a consequence of receptor phosphorylation, arrestin binding and internalization. Following activation, TRH receptors are phosphorylated at multiple Ser/Thr residues in the cytoplasmic tail. Phosphorylation catalyzed by GPCR kinase 2 (GRK2) takes place rapidly, reaching a maximum within seconds. Arrestins bind to two phosphorylated regions, but only arrestin bound to the proximal region causes desensitization and internalization. Phosphorylation at Thr365 is critical for these responses. TRH receptors internalize in clathrin-coated vesicles with bound arrestin. Following endocytosis, vesicles containing phosphorylated TRH receptors soon merge with rab5-positive vesicles. Over approximately 20 minutes these form larger endosomes rich in rab4 and rab5, early sorting endosomes. After TRH is removed from the medium, dephosphorylated receptors start to accumulate in rab4-positive, rab5-negative recycling endosomes. The mechanisms responsible for sorting dephosphorylated receptors to recycling endosomes are unknown. TRH receptors from internal pools help repopulate the plasma membrane. Dephosphorylation of TRH receptors begins when TRH is removed from the medium regardless of receptor localization, although dephosphorylation is fastest when the receptor is on the plasma membrane. Protein phosphatase 1 is involved in dephosphorylation but the details of how the enzyme is targeted to the receptor remain obscure. It is likely that future studies will identify biased ligands for the TRH receptor, novel arrestin-dependent signaling pathways, mechanisms responsible for targeting kinases and phosphatases to the receptor, and principles governing receptor trafficking.